New partners of TKS4 scaffold protein - Kropyvko, S.V. (Вiopolymers and Cell, 2015)
TKS4 scaffold protein is involved in the formation of invadopodia, the production of reactive oxygen species (ROS) by tumor cells and other cellular processes. Aim. To identify new TKS4 partners involved in the actin cytoskeleton rearrangements and endo-/exocytosis. Methods. The GST pull-down assay was used to identify the interaction. Results. We revealed that TKS4 SH3 domains interact with the actin cytoskeleton reorganization proteins N-WASP and CR16, as well as with DNM2, SYNJ1 and OPHN1 which are involved in endo-/exocytosis. We also tested the WIP, WIRE, SHIP2, RhoU, RhoV and NUMB proteins, but their interaction with the SH3 domains of TKS4 was not found. Conclusions. The SH3 domains of TKS4 interact with N-WASP, DNM2, SYNJ1, OPHN1 and weakly with CR16 in vitro.